Analisis Pengaruh Variasi Kontaminasi Air Laut Terhadap Perubahan pH dan Sifat Reologi Lumpur Pemboran pada Sumur IM Lapangan ME - Indah Mentari Ephiphania; Mirza Mirza; Esterina Natalia Paindan; Baiq Maulinda Ulfah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Drilling mud plays an important role in oil and gas drilling operations as it functions to transport cuttings, maintain wellbore stability, and control formation pressure. The performance of drilling mud may deteriorate due to contamination, one of which is seawater contamination that can affect the pH value and rheological properties of the drilling mud. This study aims to analyze the effect of seawater contamination on the pH and rheological properties of drilling mud used in Well